Thermophilic Enterococcus faecium QU 50 enabled open repeated batch fermentation for l-lactic acid production from mixed sugars without carbon catabolite repression. Issue 39 (3rd May 2017) - Tan, J.; Abdel-Rahman, M. A.; Numaguchi, M.; Tashiro, Y.; Zendo, T.; Sakai, K.; Sonomoto, K.
Abstract : Thermophilic lactic acid bacterium enabled homo-l -lactic acid fermentation from hexose/pentose without carbon catabolite repression, and open repeated production by immobilization. Abstract : Enterococcus faecium QU 50, a novel thermophilicl -lactic acid (LA) producing strain, was used in this study to ferment sugar mixtures into LA. Under the optimal fermentation conditions (50 °C, pH 6.5), strain QU 50 could ferment both mixed glucose/xylose sugars with relaxed CCR and mixed cellobiose/xylose sugars simultaneously without CCR to produce homol -LA. The activity of enzymes related to xylose metabolism was also investigated. In the cells grown in a medium containing cellobiose/xylose, the activity of xylose isomerase and xylulose kinase, was 3.22 and 1.91 times higher, respectively, as compared to that of cells grown in a glucose/xylose medium. Strain QU 50 produced 70.8 g L −1 ofl -LA with a yield of 1.04 g g −1 and a productivity of 2.95 g L −1 h −1 from simulated energy cane hydrolysate in batch fermentation. Immobilisation of strain QU 50 improved the operational stability of open repeated fermentation (three cycles), resulting in 61.1–64.3 g L −1 ofl -LA with a yield of 1.01–1.02 g g −1 and a productivity of 3.22–3.82 g L −1 h −1 . Thus, an efficient and cost-effective fermentation system was successfully established forl -LA production from sugar mixtures.